A novel lytic phage infecting MDR Salmonella enterica and its application as effective food biocontrol - Jaglan, Anu Bala; Verma, Ravikant; Vashisth, Medhavi; Virmani, Nitin; Bera, B. C.; Vaid, R. K.; Anand, Taruna (Frontiers in Microbiology, 2024)
Salmonella enterica is a foodborne pathogen associated with both typhoid and nontyphoid illness in humans and animals. This problem is further exacerbated by the emergence of antibiotic resistant strains of Salmonella enterica. Therefore, to meet the public health and safety there is a need of an alternative strategy to tackle antibiotic resistant bacteria. Bacteriophages or the (bacterial viruses) due to their specificity, self-dosing, and anti-biofilm activity, served as a better approach in fighting against drug resistant bacteria. In the current study a broad host range lytic phage phiSalP219 was isolated against multidrug resistant Salmonella enterica serotypes Paratyphi from pond water sample. Salmonella phage phiSalP219 showed infection ability in was able to lyse 28/30 tested strains of Salmonella enterica. Salmonella phage phiSalP219 exhibits activity in acidic environment (pH3) and high temperature (70°C). Electron microscopy and genome analysis revealed that phage phiSalP219 is the member of class Caudoviricetes. Genome of Salmonella phage phiSalP219 is 146.6kKb in size with 44.5% GC content. A total of 250 CDSORFs and 256 tRNAs were predicted in its genome. Predicted ORFs were divided into five groups based on their annotation results: (1) Nucleotide metabolism, (2) DNA replication and transcription, (3) Structural proteins, (4) Lysis protein, and (5) other proteins. Absence of lysogeny related genes in their genome indicate that Salmonella phage phiSalP219 is lytic in nature. Phage phiSalP219 was also found to be microbiologically safe (due to the absence of toxin or virulence related genes) in the control of Salmonella enterica serovar Typhimuriumtyphimurium infections in the ready to eat meat and also able to eradicate biofilm formed by the same bacterium on the borosilicate glass surface.